1981
DOI: 10.1007/bf02263613
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of amino acid transport in rats with experimental hyperphenylalaninaemia

Abstract: Liver and brain cortex slices from rats made hyperphenylalaninaemic with p-chlorophenylalanine showed decreased leucine uptake but increased uptake of tryptophan and glycine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Neither of these suggestions explains, however, why amino acids come to be sequestered in tissues other than brain. Zanic-Grubisic & Lipovac (1981) showed that phenylalanine excess decreases influx ofthree 14C-labelled amino acids into both liver and brain. This response by the liver we would expect only to compensate for the response by the brain.…”
Section: All Lett Ersmentioning
confidence: 99%
“…Neither of these suggestions explains, however, why amino acids come to be sequestered in tissues other than brain. Zanic-Grubisic & Lipovac (1981) showed that phenylalanine excess decreases influx ofthree 14C-labelled amino acids into both liver and brain. This response by the liver we would expect only to compensate for the response by the brain.…”
Section: All Lett Ersmentioning
confidence: 99%
“…The presence of increased blood levels of this amino acid induces the following metabolic modifications: inhibition of the activity of enzymes, such as pyruvate kinase, glutamic carboxylase and tyrosine and tryptophane hydroxylase; modification of the transport process of amino acids through the cell mem branes and increase in energetic needs, par ticularly at the level of the brain. This last condition has been studied in detail by the group of Lipovac [13,14] who demonstrated a deep involvement of the carbohydrate me tabolism in the hyperphenylalaninémie con dition. The increase of energetic needs is associated with a rapid exhaustion of liver glycogen, an increased utilization of amino acids for the gluconeogenesis, an elevated ac tivity of glucose-6-phosphatase and an in creased activity of the pentose phosphate pathway, necessary to supply NADPH for the phenylalanine hydroxylase.…”
Section: Methodsmentioning
confidence: 99%